Complexity Thinking as a Tool to Understand the Didactics of Psychology - Harmat, László; Herbert, Anna (Frontiers in Psychology, 2020)
The need to establish a research field within psychology didactics at secondary level has recently been voiced by several researchers internationally. An analysis of a Swedish case coming out of secondary level education in psychology presented here provides an illustration that complexity thinking – derived from complexity theory – is uniquely placed to consider and indicate possible solutions to challenges, described by researchers as central to the foundation of a new field. Subject-matter didactics is defined for the purpose of this paper as a combination of general didactics and subject- matter content, and considering the international nature of research traditions coming out of psychology, the implications of the results presented here cannot be regarded as limited solely to national concerns. An on-line survey was sent to secondary schools in Sweden. Discussions and lectures along with teaching to the book – alternatively used as inspiration – emerged as central from the thematic analysis of the results, providing the first mapping of teaching practices in secondary level psychology in Sweden. An analysis, founded on complexity thinking – combined with a model enabling a delimitation of the scope of study – focused on time use and the importance placed on self-knowledge, along with the transformation of theory into practice. The former pointing to a teacher centred nested subsystem (e.g. asymmetric relations between teachers and students), the latter pointing to student centred nested subsystems coming out of embodied knowledge (e.g. students as node) where psychological perspectives are learnt through self-reflexion, case studies and everyday life experiences (turning theory to practice), implying a holistic approach. The analysis applied to the Swedish case provides an illustration of how complexity theory has the potential to address challenges at micro and macro level to the establishment of a new research field in psychology didactics and to indicate possible solutions. Psychologies high relevance to everyday life, multi-causality, perspective pluralism, dynamic systems character and scientific character, makes complexity thinking a relevant approach in the consideration of challenges to the establishment of a research field in didactics of psychology.